2015
DOI: 10.4996/fireecology.1101119
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Ash and Black Carbon (Biochar) on Germination of Different Tree Species

Abstract: Forest fires generate large amounts of ash and biochar, or black carbon (BC), that cover the soil surface, interacting with the soil’s constituents and its seedbank. This study concerns reproductive ecology assessments supported by molecular characterisation to improve our understanding of the effects of fire and fire residues on the germination behaviour of 12 arboreal species with a wide geographic distribution. For this purpose, we analysed the effects of three ash and one BC concentration on the germinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…The seeds were incubated in Petri dish with 0.26 g of charcoal (411 kg ha -1 ) per replicate of the corresponding species. Such amount of charcoal is the same as that measured by Ohlson & Tryterud (2000) in boreal forest fires of Scandinavia and in other studies in Spain (Reyes et al 2015b). Ash treatments were ash1 (0.027 g/replicate, 43.5 kg ha -1 ), ash2 (0.055 g/replicate, 87 kg ha -1 ), ash3 (0.11 g/replicate, 174 kg ha -1 ), ash4 (0.275 g/replicate, 435 kg ha -1 ) and ash5 (0.55 g/replicate, 870 kg ha -1 ).…”
Section: Methodssupporting
confidence: 88%
See 1 more Smart Citation
“…The seeds were incubated in Petri dish with 0.26 g of charcoal (411 kg ha -1 ) per replicate of the corresponding species. Such amount of charcoal is the same as that measured by Ohlson & Tryterud (2000) in boreal forest fires of Scandinavia and in other studies in Spain (Reyes et al 2015b). Ash treatments were ash1 (0.027 g/replicate, 43.5 kg ha -1 ), ash2 (0.055 g/replicate, 87 kg ha -1 ), ash3 (0.11 g/replicate, 174 kg ha -1 ), ash4 (0.275 g/replicate, 435 kg ha -1 ) and ash5 (0.55 g/replicate, 870 kg ha -1 ).…”
Section: Methodssupporting
confidence: 88%
“…In addition, Ulex charcoal strongly delayed the germination of seeds from Y trees. Other studies revealed negative (Buss & Mašek 2014), neutral (Reyes & Casal 2006) or positive effects of charcoal (Reyes et al 2015b), suggesting that charcoal effect could depend on its nature and on the exposed species.…”
Section: Iforest -Biogeosciences and Forestrymentioning
confidence: 97%
“…Similar differences were observed in CWD between burned and harvested areas with most CWD in harvested areas containing small pieces/fragments of wood [29], which are similar to our reclaimed sites. Charring of CWD and the production of black carbon in the midst of fires may also impact the germination of native plants [30], but the response tends to be variable by species. Therefore, quantifying the CWD profile [31] including the species, size, decay class, charring, and more than total volume may allow more subtle differences to be detected.…”
Section: Discussionmentioning
confidence: 99%
“…In other leguminous species, charcoal inhibition of germination was not found either, such as Acacia dealbata Link. and A. melanoxylon [70] or T. angustifolium and R. sphaerocarpa [91]. The charcoal effect seem to depend on the nature of the charcoal [70].…”
Section: Fire Factors Effectsmentioning
confidence: 93%
“…The seeds were incubated in Petri dishes on 0.26 g (411 kg/ha) of charcoal from the corresponding species. This is the equivalent amount of charcoal measured by Ohlson and Tryterud [69] after experimental fires in the boreal forests of Scandinavia and is the dose used in previous works [70].…”
Section: Viability and Germinationmentioning
confidence: 99%